The impact of China's urban and rural economic revitalization on the utilization of mental health inpatient services - Yan, Yu; Tu, Yongqian (Frontiers in Public Health, 2023)
Background Rural locations have a lower preference for mental healthcare than urban areas. Medical and pharmacy expenses incurred as a result of serious mental illness are covered by public health insurance, according to the People's Republic of China's Mental Health Law. This study aimed to acknowledge the disparities in the use of mental health services provided by the government health schemes among the rural and urban populations of China and to assess the real reimbursement rates for health insurance coverage. It also sheds light on China's ongoing healthcare reforms for mental health treatments. Materials and methods A retrospective cohort study of patients was conducted that were hospitalized with mental illnesses to assess rural–urban disparities in the utilization of mental health services and the role of health insurance. We used electronic health data from the major psychiatric institutes for 15 years (2005–2020) to assess the influence of health insurance systems on Chinese public preferences for mental health treatments. These psychiatric hospitals serve almost 10% of all mental health patients every year in Shandong and accept patients from all over the country. In addition, health insurance policy regulations in Shandong Province are consistent with national health insurance policy regulations. Models 1 and 2 assess disparities in the utilization of mental health treatments. Our study population was identified using patients' primary diagnosis, as recorded in the two hospitals' EHRs, which routinely record information on patients' sociodemographic characteristics, clinical characteristics of the disease, cost of the treatment, and type of the health insurance plan. The record of EHR data is considered efficient because they document all inpatient expenses incurred during hospitalization in a detailed, itemized, and reliable way. Results Urban patients had longer hospital stays (p = 0.0001), more hospitalizations (p = 0.006), and greater hospitalization expenses (p = 0.001) than rural patients. Patients who had insurance had a longer hospital stay (p = 0.0001), more hospitalizations (p = 0.0001), and greater hospitalization costs (p = 0.0001) than those who did not have insurance. Urban residents used mental health services more than rural residents. People preferred mental healthcare when the reimbursement ratio variable was larger, especially in rural areas. Conclusion Rural people of China experience mental health services are an economic burden. Uniform measures are required to be taken for the development of health insurance policies for people in rural areas.